2018
DOI: 10.1038/s41598-018-33583-9
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and carriage of Streptococcus pneumoniae serotypes in Danish children, a double-blind randomized controlled trial

Abstract: This study examined the carriage of Streptococcus pneumoniae in healthy Danish children aged 8–19 months and assessed the effect of the probiotics Lactobacillus rhamnosus GG and Bifidobacterium animalis subsp lactis on the pneumococcal carriage during daycare enrolment. Potential risk factors of pneumococcal carriage were analysed and the carriage study was compared with registered invasive pneumococcal disease (IPD) data. This study is a part of the ProbiComp study, which was a double-blind, randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Streptococcus pneumoniae (pneumococcus) is considered the leading pathogen associated with community-acquired pneumonia, otitis media and meningitis [1]. Pneumococcal appearance in humans can be divided into two phases, carriage and the disease phase, where the carriage of S. pneumoniae is generally described as the prerequisite for developing pneumococcal infections, and often young children are considered to act as reservoirs [2, 3]. Pneumococcal infections have attracted global public health attention due to the high burden of disease and associated mortality, particularly among children under five and adults > 64 years in resource poor countries [1, 4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus pneumoniae (pneumococcus) is considered the leading pathogen associated with community-acquired pneumonia, otitis media and meningitis [1]. Pneumococcal appearance in humans can be divided into two phases, carriage and the disease phase, where the carriage of S. pneumoniae is generally described as the prerequisite for developing pneumococcal infections, and often young children are considered to act as reservoirs [2, 3]. Pneumococcal infections have attracted global public health attention due to the high burden of disease and associated mortality, particularly among children under five and adults > 64 years in resource poor countries [1, 4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study 10 we found that children living with siblings had a significant higher carriage rate of S. pneumoniae compared to only children. In this study, we assessed the PCV13 antibody response in children with and without siblings as novel information and found that at baseline there was no significant statistical difference in the PCV13 antibody response when compared children with and without siblings (p = 0.157), but having siblings increased the PCV13 antibody response (µg/mL) at the end of study (p = 0.0135) (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Previous studies show no statistical significance between the probiotics group and the placebo group when comparing carriage rate of pneumococcal serotypes and no significant difference in antibody response to PCV13 8,10 . Furthermore, no significant differences between the groups were seen in terms of gender, siblings, breastfeeding, indoor pets, health status since birth, smoking in the household, age or compliance 18 , thus the two groups were compiled for analyses in this study (Table 1).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations